HUMAN AS A NEVER-ENDING PROBLEM: THE GENEALOGY OF THE CRISIS IN PHILOSOPHICAL ANTHROPOLOGY AND THE PARADOX OF THE INDONESIAN SUBJECT — FROM ZOON LOGON ECHON TO ALGORITHMIC CITIZEN - Ihsan Aladin (Sadra International Institute, 2026)
One of the central themes in contemporary philosophy is the crisis of modern human anthropology, namely the reduction of human meaning due to technocracy, rationalism, and the algorithmization of life. From the Greek philosophical concept of zoon logon echon to the modern rational subject, human beings have been understood as autonomous and thinking entities. However, with the rise of digital technologies and algorithmic systems, humans are no longer primarily seen as rational beings but rather as data objects that can be controlled, predicted, and systematically engineered. Moral, spiritual, and transcendental dimensions are increasingly called into question, thereby deepening the crisis of human meaning. From the perspective of Islamic philosophy, this article traces the development of this crisis from classical rationalism and the modern subject to the fragmentation of the subject in the algorithmic era. The study employs a philosophical-critical method with a historical-conceptual approach, complemented by a hermeneutic analysis of Islamic philosophical texts and normative sources. The findings indicate that, in Islamic thought, the human being is a person of integrity, situated within an ontological tension between spirituality and reason, freedom and responsibility. Humans are understood as open-ended ethical-spiritual projects rather than fully deterministic entities. Islam thus offers a fundamental critique of algorithmic reductionism by emphasizing the centrality of monotheism, intention, and moral consciousness in anthropology.